The dual‐functional memantine nitrate MN‐08 alleviates cerebral vasospasm and brain injury in experimental subarachnoid haemorrhage models. (31st July 2019) - Luo, Fangcheng; Wu, Liangmiao; Zhang, Zhixiang; Zhu, Zeyu; Liu, Zheng; Guo, Baojian; Li, Ning; Ju, Jun; Zhou, Qiang; Li, Shupeng; Yang, Xifei; Mak, Shinghung; et al.
Abstract : Background and Purpose: Cerebral vasospasm and neuronal apoptosis after subarachnoid haemorrhage (SAH) is the major cause of morbidity and mortality in SAH patients. So far, single‐target agents have not prevented its occurrence. Memantine, a non‐competitive NMDA re3ceptor antagonist, is known to alleviate brain injury and vasospasm in experimental models of SAH. Impairment of NO availability also contributes to vasospasm. Recently, we designed and synthesized a memantine nitrate MN‐08, which has potent dual functions: neuroprotection and vasodilation. Here, we have tested the therapeutic effects of MN‐08 in animal models of SAH. Experimental Approach: Binding to NMDA receptors (expressed in HEK293 cells), NO release and vasodilator effects of MN‐08 were assessed in vitro. Therapeutic effects of MN‐08 were investigated in vivo, using rat and rabbit SAH models. Key Results: MN‐08 bound to the NMDA receptor, slowly releasing NO in vitro and in vivo. Consequently, MN‐08 relaxed the pre‐contracted middle cerebral artery ex vivo and increased blood flow velocity in small vessels of the mouse cerebral cortex. It did not, however, lower systemic blood pressure. In an endovascular perforation rat model of SAH, MN‐08 improved the neurological scores and ameliorated cerebral vasospasm. Moreover, MN‐08 also alleviated cerebral vasospasm in a cisterna magna single‐injection model in rabbits. MN‐08 attenuated neural cell apoptosis in both rat and rabbit models of SAH. Importantly, the therapeutic benefit of MN‐08 was greater than that of memantine. Conclusion and Implications: MN‐08 has neuroprotective potential and can ameliorate vasospasm in experimental SAH models.